Types, stability, and phenotypic consequences of chromosome rearrangements leading to interstitial telomeric sequences. Issue 11 (November 1993) - Rossi, E; Floridia, G; Casali, M; Danesino, C; Chiumello, G; Bernardi, F; Magnani, I; Papi, L; Mura, M; Zuffardi, O
Abstract : Using in situ hybridisation, we identified interstitial telomeric sequences in seven chromosomal translocations present in normal and in syndromic subjects. Telomeric sequences were also found at the centromeric ends of a 4p and a 4q caused by centric fission of one chromosome 4. We found that rearrangements leading to interstitial telomeric sequences were of three types: (1) termino-terminal rearrangements with fusion of the telomeres of two chromosomes, of which we report one case; (2) rearrangements in which an acentric fragment of one chromosome fuses to the telomere of another chromosome. We describe four cases of Prader-Willi syndrome with the 15q1-qter transposed to the telomeric repeats of different recipient chromosomes; (3) telomere-centromere rearrangements in which telomeric sequences of one chromosome fuse with the centromere of another chromosome. We describe two examples of these rearrangements in which not only telomeric sequences but also remnants of alphoid sequences were found at the fusion point. Instability at the fusion point of the derivative chromosome was found in the Prader-Willi translocations but we were unable to correlate this instability with culture conditions. The two subjects with the termino-terminal rearrangement and the centric fission respectively have normal phenotypes. The two patients with telomere-centromere fusions were unbalanced for the short arm of an acrocentric chromosome and had failure to thrive; one of them also had dysmorphic facies. We postulate that these phenotypes could be the result of uniparental disomy.